A descriptive analysis of anglicisms Used in ecuadorian magazines - Infante Paredes, Alicia Mercedes (2012)
This paper aims at carrying out a descriptive and linguistic analysis of the use of Anglicisms in Ecuadorian Magazines. In order to do so, three variables were used for this investigation. Such variables are: Scholarly, Cultural, and General Interest Ecuadorian magazines. Each variable includes magazines same that have been printed and edited in Ecuador. The two scholarly magazines selected for this investigation were “Gestión” and “Américaeconomía”, Cultural magazines number 28 and 29 were obtained from “La Casa de la Cultura Benjamín Carrión, Núcleo de Chimborazo,” finally, “Vistazo” and “”Hogar” were the magazines selected for the General Interest category. In terms of the place of investigation, the magazines were obtained in Quito, Ambato, and Riobamba. It is also worth mentioning that this study will use Qualitative and Quantitative methods in order to analyze Anglicisms obtained from the above mentioned magazines and how they are used in the Spanish language. It is also undeniable, the fact that English is a global language and therefore it is used in many places around the world. Due to the significance of this language, many English terms have been adapted to other languages. In this sense, Spanish is one of the languages that have been influenced by English terms on its lexicon.